Measurement Natural Radioactivity in Soil Samples from Important historical locals in Alnajaf Alashraf city, Iraq. - Majeed, Heiyam N.; Hasan, Ali K.; Hamad, Hussein J. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Al-Najaf Al-Ashraf city one of the most important ,oldest, historical and religious cities in Iraqi country which includes hundreds of holy shrines and historical mosques which over the built hundreds of years. The natural radiation of forty two samples of soil which collected randomly in June 2013 from different religious and historical places were measured using 3"×3" Na(Tl) detection. The mean values activity concentrations of 238U, 232Th and 40K was ( 23.59±4.37, 12.10±0.54 and 60.68±2.30) Bq kg-1 respectively , specific activity for all soil sample were in the worldwide average. The average values of the Radium equivalent activity and annual effective dose were (22.455 Bq/kg and 25.375 μSv/y) less than the world average .The heist external and internal hazard and gamma activity concentration index were (0.274 , 0.412 and 0.705) lower than unity.